The History of Paulina - Francisco Herrera-Rodríguez (Universidad de Alicante, 2016)
Carmen Chamizo Vega is a point of reference in Spanish Nursing and more concretely in the History of Nursing. Her teaching, care and research labour will continue marking the future as well as her untiring work by establishing networks and communication links among scholars of Nursing in Spain and America. Carmen, in a discreet and serene way has left from our lives for a while. With the present writing, named after one of her stories, I want to pay tribute to her without academic panegyric, only appealing to the excitement of memory.